Exploratory evaluation of variation in statin take up amongst high risk patients in Nottingham City - Shaw, Ian; Turner, Andrew (Nottingham City Clinical Commissioning Group, 2012)
This report is from a small qualitative study evaluating variation in statin take up following risk assessment as part of the UK's NHS Health Checks programme. Previous studies at the practice level have found lower than expected take up of statins from the Health Checks programme, and it has been suggested that this may be due to patients' and doctors' beliefs about treating risk rather than disease⁠. From interviews with a small sample of patients and GPs we suggest that greater variation may be a consequence of shared-decision making. The trends we identified have implications for primary care practice, if corroborated in a large study. Our results therefore provide a basis for further research in this area.